1997
DOI: 10.1016/s0954-6111(97)90033-0
|View full text |Cite
|
Sign up to set email alerts
|

Overlooked inhaled foreign bodies: late sequelae and the likelihood of recovery

Abstract: The present paper describes eight patients (two teenagers and six adults) who had chronic symptoms (haemoptysis, cough, recurrent pneumonia) caused by foreign body (FB) inhalation which went undetected for 3 months to 25 yr. None of the patients had the usual predisposing conditions like mental retardation, seizures or brain tumour. The diagnosis of FB was made by radiography in one patient only. Computerized tomography visualized one FB (a beef bone), and bronchoscopy identified FB in another two patients. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0
4

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(64 citation statements)
references
References 8 publications
2
58
0
4
Order By: Relevance
“…Although paroxysmal cough, wheezing and decreased breath sounds are the cardinal symptoms and signs of foreign body inhalation, they are present only in a limited number of cases [13,21] and may be absent in others [4,6,19]. In extreme cases, a foreign body may remain asymptomatic for up to 25 years [2]. As the diagnosis is too often missed by clinicians, a high level of suspicion is necessary and requires a detailed history and careful physical examination.…”
Section: Discussionmentioning
confidence: 99%
“…Although paroxysmal cough, wheezing and decreased breath sounds are the cardinal symptoms and signs of foreign body inhalation, they are present only in a limited number of cases [13,21] and may be absent in others [4,6,19]. In extreme cases, a foreign body may remain asymptomatic for up to 25 years [2]. As the diagnosis is too often missed by clinicians, a high level of suspicion is necessary and requires a detailed history and careful physical examination.…”
Section: Discussionmentioning
confidence: 99%
“…The longer the FB is retained, the more likely are complications (e.g., atelectasis, post-obstructive pneumonia). A FB that causes chronic or recurrent distal infection may lead to bronchiectasis (31,39,40,59,60). This complication should be treated after the FB is abstracted.…”
Section: Complicationsmentioning
confidence: 99%
“…However, a history of FB aspiration might not be obvious, and the related symptoms, such as chronic cough, dyspnea and hemoptysis for most adult patients could remain unnoticed for months to years (1,2). The delayed diagnosis of FBs may lead to serious complications such as granulation formation, recurrent pneumonia, atelectasis and endobronchial stenotic scarring (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%
“…The extraction of FBs using a flexible bronchoscope is one of the most commonly used techniques (3,6,7). A few published studies have described the clinical features and endoscopic management of tracheobronchial FBs (2,3,(5)(6)(7)(8)(9)(10). However, the sample sizes of these studies were small, and few of them reported the management of the complications of FBs aspiration.…”
Section: Introductionmentioning
confidence: 99%